The ethics of crowdfunding in paediatric neurology. (21st October 2022) - Livingstone, Angus; Servais, Laurent; Wilkinson, Dominic J. C.
Abstract: In the last decade, there has been a dramatic increase in the number of families resorting to internet‐based public appeals to fund access to novel, highly expensive, or experimental therapies for rare disorders. Medical crowdfunding may provide a means to fund treatments or interventions, but it raises individual and societal ethical questions. In this review, we consider the ethical challenges crowdfunding poses in paediatric neurology, drawing on the example of gene therapy for spinal muscular atrophy. We discuss physician responsibilities, and how neurologists should respond to crowdfunding that they encounter in clinical practice. We also briefly consider actions that can be taken by clinicians, charities, and crowdfunding websites to reduce harms. The best way to mitigate these harms may be to target the high costs and restrictive criteria that limit access to many novel treatments, and to optimize treatment utility, for instance by newborn screening. What this paper adds: Crowdfunding is a social phenomenon arising from families' inability to access desired treatment. Treatments sought by crowdfunding range from those that are clearly beneficial (but unaffordable) to those that would be ineffective and potentially harmful. Crowdfunding carries a range of harms and risks to families and children and has wider social impact. What this paper adds: Crowdfunding is a social phenomenon arising from families' inability to access desired treatment. Treatments sought by crowdfunding range from those that are clearly beneficial (but unaffordable) to those that would be ineffective and potentially harmful. Crowdfunding carries a range of harms and risks to families and children and has wider social impact.